Economic and Financial Benchmarking as a Strategic Planning Tool - Intrisano, Carmelo; Micheli, Anna Paola; Calce, Anna Maria; Di Nallo, Loris (International Journal of Economics and Financial Issues, 2017)
This paper aims to propose a new model for estimating companies benchmarking. The model has been applied to the media sector (identified by Industry Classification Benchmark – ICB with the code 5500 and composed by three subsector with codes: 5553 – Broadcasting & Entertainment, 5555 – Media Agencies and 5557 – Publishing). The model is based on the analysis of the financial and economic area of enterprises that together contribute to the elaboration of a total benchmark. We collected data for 217 listed companies for a time horizon of ten years (2006-2015). The results show that most of the analyzed companies belong to the best or worst class. Deepening the analysis, the subsector 5555 – Media agencies has contributed most to the positive performance of the media sector while the subsector 5553 - Broadcasting & Entertainment is the worst. The model, applied to the media industry, can be extended to other sectors and unlisted companies. Keywords: benchmark, strategy planning, finance. JEL Classification: G